BABI DALAM BUDAYA PAPUA (Pig in The Papua Culture) - Hari Suroto (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2014)
The pig is an integral part of the culture in the highlands of Papua. Nevertheless, to this day still happening cross of opinion among experts about when the first swine entered in Papua. This paper will discuss the beginning of pigs in Papua and Papuan cultural values associated with the presence of a pig. Data was collected with a literature study, in this paper used descriptive qualitative method. Beginning of the presence of swine in Papua brought by Austronesian speakers. Pig bones found in cave sites north coast of Papua. The presence of pigs in Papua are very influential in Papuan culture. ABSTRAKBabi merupakan bagian yang tak terpisahkan dari budaya di daerah dataran tinggi Papua. Meskipun demikian, sampai hari ini masih saja terjadi persilangan pendapat antar para ahli mengenai kapan pertama kali babi masuk di Papua. Tulisan ini akan membahas awal mula babi di Papua dan nilai-nilai budaya Papua yang terkait dengan keberadaan babi. Teknik pengumpulan data dilakukan dengan studi kepustakaan, dalam tulisan ini digunakan metode deskriptif kualitatif. Awal mula keberadaan babi di Papua dibawa oleh penutur Austronesia. Tulang-tulang babi ditemukan di situs-situs gua pesisir utara Papua. Keberadaan babi di Papua sangat berpengaruh pada budaya Papua.